Case of Covid-19 co-infection with Crimean Congo haemorrhagic fever (CCHF) in a CCHF endemic country: a case report - Musani, Sadaf Hanif; Alam, Muhammad Mehmood; Latif, Asad (Journal of the Pakistan Medical Association, 2023)
Covid-19 pandemic affected the health care systems globally. In many countries, healthcare services were overwhelmed by the huge number of Covid cases; hence, shifting the focus from locally endemic infectious diseases. Such a case presented to us that was initially managed along the lines of critical Covid pneumonia with steroids, Remdesivir, and supplemental oxygen for hypoxic respiratory failure. The patient also received Baricitinib, to which he was non-responsive and thus offered invasive mechanical ventilation. Post intubation, the patient was managed for Covid-associated ARDS with lung protective ventilation. He later also developed liver dysfunction, renal failure, coagulation derangements, and shock. Workup for malaria and dengue were negative. Later, Crimean Congo PCR was sent which came positive; a possible cause of progressive deterioration. In CCHF endemic areas, it is crucial to rule out the CCHF infection among patients presenting with critical Covid pneumonia due to similar clinical presentation in both the infections.